Analisis Yuridis Penggunaan Akta Perjanjian Pra Perceraian sebagai Alat Bukti Pengadilan - Nabila Aida Farhana Lubdin; Arief Suryono (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
Divorce gives rise to various legal consequences relating to the status of the parties, marital property, and the rights and obligations toward children, thereby requiring a legal mechanism that ensures legal certainty, justice, and legal protection. In practice, the parties often express their intention to divorce in the form of a Pre-Divorce Agreement Deed drawn up before a notary. This study aims to analyze the legal standing and evidentiary strength of a Pre-Divorce Agreement Deed as evidence in divorce cases decided by default judgment (verstek). The research employs a normative juridical method with a statutory approach and a case approach, focusing on the Decision of the Ngawi Religious Court Number 425/Pdt.G/2023, through a literature review of primary and secondary legal materials. The findings indicate that a Pre-Divorce Agreement Deed executed in the form of a notarial deed constitutes an authentic deed with perfect evidentiary value as written evidence in divorce proceedings. Although it cannot directly result in the dissolution of marriage, the deed is relevant to prove the existence of an agreement between the parties and the condition of a marital relationship that has irretrievably broken down. In cases decided by default judgment, the deed becomes an important basis for judicial consideration in granting the divorce petition. The implications of this study emphasize that a Pre-Divorce Agreement Deed may be lawfully and proportionately used as evidence to support the proof of grounds for divorce and to realize legal certainty in judicial proceedings.